Two-Component Signal Transduction System SaeRS Positively Regulates Staphylococcus epidermidis Glucose Metabolism - Qiang Lou; Yijun Qi; Yuanfang Ma; Di Qu (The Scientific World Journal)
Staphylococcus epidermidis, which is a causative pathogen of nosocomial infection, expresses its virulent traits such as biofilm and autolysis regulated by two-component signal transduction system SaeRS. In this study, we performed a proteomic analysis of differences in expression between the S. epidermidis 1457 wild-type and saeRS mutant to identify candidates regulated by saeRS using two-dimensional gel electrophoresis (2-DE) combined with matrix-assisted laser desorption/lonization mass spectrometry (MALDI-TOF-MS). Of 55 identified proteins that significantly differed in expression between the two strains, 15 were upregulated and 40 were downregulated. The downregulated proteins included enzymes related to glycolysis and TCA cycle, suggesting that glucose is not properly utilized in S. epidermidis when saeRS was deleted. The study will be helpful for treatment of S. epidermidis infection from the viewpoint of metabolic modulation dependent on two-component signal transduction system SaeRS.